Some characteristics of the alarm call of lapwing (Vanellus vanellus) - A N Varaksin; O L Silaeva (RUDN Journal of Ecology and Life Safety, 2015)
Using the methods of speech analysis there were examined alarm calls of three individuals of lapwing (Vanellus vanellus) belonging to three different populations. In the time domain the voice differences are manifested in prosodic features, such as the mean and variance of the basic tone, as well as the distribution of energy over time. In the spectral range the differences the peculiarities are related to the articulator apparatus, they appear in the different formant tracks movements relative to each other. Common features include. The similarity of the basic tone trajectory change, when up to 300 period, the trend of its increasing is saved, followed by a slight decline, and before the end of the signal rise again. Location of the first formant approximately on the same frequency. The similarity of movement of formant tracks. Stability of the first formant. However, to draw final conclusions on the individual, geographical and species-specific signal characteristics need a lot more statistics than there is for the moment.